2016
DOI: 10.2139/ssrn.2786971
|View full text |Cite
|
Sign up to set email alerts
|

The Distributional Consequences of Large Devaluations

Abstract: We study the differential impact of large exchange rate devaluations on the cost of living at different points on the income distribution. Across product categories, the poor have relatively high expenditure shares in tradeable products. Within tradeable product categories, the poor consume lower-priced varieties. Changes in the relative price of tradeables and the relative prices of lower-priced varieties following a devaluation will affect the cost of the consumption basket of the low-income households relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Using cross country data, Fajgelbaum and Khandelwal (2015) show that aggregate gains from trade through expenditures of individuals are substantially more at the lower end of the income distribution. Cravino and Levchenko (2015) study the impact of exchange rate devaluation in Mexico and find that relative price changes affects the consumption basket of low income households more than that of high income households. In the case of China, this paper contributes to the literature by showing that the structure of the local economy, in particular the size of the private sector, significantly affects the price transmission mechanism.…”
Section: Results For Consumption Effectsmentioning
confidence: 99%
“…Using cross country data, Fajgelbaum and Khandelwal (2015) show that aggregate gains from trade through expenditures of individuals are substantially more at the lower end of the income distribution. Cravino and Levchenko (2015) study the impact of exchange rate devaluation in Mexico and find that relative price changes affects the consumption basket of low income households more than that of high income households. In the case of China, this paper contributes to the literature by showing that the structure of the local economy, in particular the size of the private sector, significantly affects the price transmission mechanism.…”
Section: Results For Consumption Effectsmentioning
confidence: 99%
“…Results based on annual data for 1990-2015, and a gravity model estimated with the Poisson pseudo-maximum likelihood estimator, showed a consistently positive and significant effect of trade on inequality over time. Cravino and Levchenko (2017) examined the impact of large exchange rate devaluations on the cost of living at different points on the income distribution. They found that the cost of living rose for the bottom income decile, increasing 1.48-1.62 times more than for the top income decile, with changes in the relative prices of tradables and lower-priced varieties, since the bottom decile consumed more of such products.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…food). The latter introduces a non-homotheticity in consumption, which captures the fact that poor households spend a higher fraction of their income on tradables, and within tradables, on goods with systematically lower nontradable components (Cravino and Levchenko, 2017). As a result, the cost of poor households' consumption baskets is particularly sensitive to exchange rate fluctuations, which, as we discuss at great length below, has immediate consequences for central bank policies.…”
Section: Model Setupmentioning
confidence: 99%
“…The second ingredient is an inefficiency in the competitive equilibrium that makes the path of the exchange rate suboptimal absent interventions. Inspired by Cravino and Levchenko (2017), this occurs in our baseline model due to a novel pecuniary externality: rich households do not take into account the effect of their spending decisions on the purchasing power of the poor via the real exchange rate. More precisely, we build a real small open economy model with two types of households: one of them is rich and Ricardian, while the other is poor and hand-to-mouth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation